Visa A. J. Kurki and Tomasz Pietrzykowski (Eds.). Legal Personhood: Animals, Artificial Intelligence and the Unborn - The Law and Philosophy Library, Volume 119, ix (Springer International Publishing, 2017) 158 p. - Oliver Wookey (Universitat Autonoma de Barcelona. Facultat de Dret, 2018)
It is in a possible future reconstruction of the notion of legal personhood that the key to better protection for animals may lie. At least, this is the belief of those who seek to expand the current understanding of personhood to encompass animals. It is in essence of this agenda, therefore, that the collection of critical essays compiled by editors Visa A. J. Kurki and Tomasz Pietrzykowski, provide compelling deconstruction of its current legal conceptualisation and careful critique of its unsatisfactory reflection of modern philosophical thought relating to animals, artificial intelligence and the unborn, and provide some fundamental groundwork and, by extension, a great step forward, for a favourable reconceptualization of legal personhood.